REVITALIZATION OF CHURCH MUSIC THROUGH A CREATIVE ECONOMY APPROACH: STRATEGIES AND OPPORTUNITIES: Revitalisasi Musik Gereja melalui Pendekatan Ekonomi Kreatif: Strategi dan Peluang - Denny Adry Tarumingi; Mieke Nova Sendow (Proram studi pendidikan Sejarah Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
Abstract This study explores the revitalization of church music within the Minahasa Evangelical Christian Church (GMIM) through the lens of creative economy, identifying opportunities, and formulating contextually grounded development strategies. Despite rich musical traditions and high congregational competence in choral and traditional performances, these assets remain underutilized as economic resources because of the absence of professional management, digital infrastructure, and institutional policies. Employing a qualitative case study approach, data were collected through in-depth interviews, focus group discussions, direct observations, and document analysis across selected GMIM congregations in Minahasa. Thematic analysis revealed four key opportunity domains: physical products, digital content, performance services, and strategic collaboration. While digital platforms and inter-institutional partnerships offer high economic potential, their implementation is hindered by their limited technical capacity, copyright awareness, and formal revenue-sharing mechanisms. The findings indicate that current music-related activities are primarily driven by spiritual and communal motives, with economic benefits remaining incidental rather than systemic. To address this, this study proposes a four-pillar development framework of management, production, marketing, and values centered on the establishment of a church-based creative unit (“Bait Musica”), capacity-building programs, digitalization, and cultural preservation. Strategic initiatives, such as an annual Minahasan Sacred Music Festival, cooperative-based distribution, and monetized digital content, are recommended to ensure sustainability and inclusivity. Crucially, the model emphasizes ethical commercialization, ensuring that economic development aligns with spiritual integrity and communal values. This study contributes to the discourse on faith-based creative economies by demonstrating how religious institutions can serve as catalysts for local economic empowerment without compromising cultural or theological authenticity. The proposed framework offers a replicable model for other religious communities seeking to transform sacred art into sustainable community-driven enterprises.